2015
DOI: 10.1016/j.jsps.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Systemic review on drug related hospital admissions – A pubmed based search

Abstract: Most of DRP studies were retrospective, multicenter studies conducted in general populations in Europe. The main objective of the studies was to estimate DRP frequency, incidence, risk factors and trends of DRP hospital admissions. Anti-neoplastic agents, CVS drugs and CNS drugs were related to most of the drug related problems. These studies concluded polypharmacy and older age were the major risk factors for developing drug related problems. It was found that the cost for the management of DRP was directly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 19 publications
7
66
1
3
Order By: Relevance
“…In fact, using a too sensitive search strategy can result in many redundant hits and initially increase the researcher's workload. However, our number of hits was consistent more with that of a recent systematic review on drug related hospital admission, made using PubMed by Nivya et al covering the period between 2007-2013, and they found only (366) initial hits [5].…”
supporting
confidence: 91%
“…In fact, using a too sensitive search strategy can result in many redundant hits and initially increase the researcher's workload. However, our number of hits was consistent more with that of a recent systematic review on drug related hospital admission, made using PubMed by Nivya et al covering the period between 2007-2013, and they found only (366) initial hits [5].…”
supporting
confidence: 91%
“…The most age was represented the eighty-eight percent of responders. There is no statistically significant between all age categories between patient and healthcare professionals expert in the age (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) years. The complete most healthcare professionals were pharmacist 34 (65.38%), and nurses were six (11.54%) followed by others 5 (9.62%), dentist 4 (7.69%) and 3 (5.77%) physicians.…”
Section: Resultsmentioning
confidence: 99%
“…However, the frequency of DRMs has varied widely from 0.2% to 65% in individual studies (38,40,41), due to differing study designs and settings, study populations, and detection methods of DRMs (39,42). Moreover, DRMs are found more often among the elderly and persons with multiple medications (38,(43)(44)(45).…”
Section: Drug-related Morbiditiesmentioning
confidence: 99%